Circulating cell‐free messenger RNA enables non‐invasive pan‐tumour monitoring of melanoma therapy independent of the mutational genotype. Issue 11 (1st November 2022) - Albrecht, Lea Jessica; Höwner, Anna; Griewank, Klaus; Lueong, Smiths S.; von Neuhoff, Nils; Horn, Peter A.; Sucker, Antje; Paschen, Annette; Livingstone, Elisabeth; Ugurel, Selma; Zimmer, Lisa; Horn, Susanne; et al.
Abstract: Background: Plasma‐derived tumour‐specific cell‐free nucleic acids are increasingly utilized as a minimally invasive, real‐time biomarker approach in many solid tumours. Circulating tumour DNA of melanoma‐specific mutations is currently the best studied liquid biopsy biomarker for melanoma. However, the combination of hotspot genetic alterations covers only around 80% of all melanoma patients. Therefore, alternative approaches are needed to enable the follow‐up of all genotypes, including wild‐type. Methods: We identified KPNA2, DTL, BACE2 and DTYMK messenger RNA (mRNA) upregulated in melanoma versus nevi tissues by unsupervised data mining ( N  = 175 melanoma, N  = 20 normal skin, N  = 6 benign nevi) and experimentally confirmed differential mRNA expression in vitro ( N  = 18 melanoma, N  = 8 benign nevi). Circulating cell‐free RNA (cfRNA) was analysed in 361 plasma samples (collected before and during therapy) from 100 melanoma patients and 18 healthy donors. Absolute cfRNA copies were quantified on droplet digital PCR. Results: KPNA2, DTL, BACE2 and DTYMK cfRNA demonstrated high diagnostic accuracy between melanoma patients' and healthy donors' plasma (AUC > 86%, p  < .0001). cfRNA copies increased proportionally with increasing tumour burden independently of demographic variables and even remained elevated in individuals with radiological absence of disease. Re‐analysis of single‐cell transcriptomes revealed a pan‐tumour origin of cfRNA, including endothelial, cancer‐associated fibroblasts, macrophages and B cells beyond melanoma cells as cellular sources. Low baseline cfRNA levels were associated with significantly longer progression‐free survival (PFS) ( KPNA2 HR = .54, p  = .0362; DTL HR = .60, p  = .0349) and overall survival ( KPNA2 HR = .52, p  = .0237; BACE2 HR = .55, p  = .0419; DTYMK HR = .43, p  = .0393). Lastly, we found that cfRNA copies significantly increased during therapy in non‐responders compared to responders regardless of therapy and mutational subtypes and that the increase of KPNA2 (HR = 1.73, p  = .0441) and DTYMK (HR = 1.82, p  = .018) cfRNA during therapy was predictive of shorter PFS. Conclusions: In sum, we identified a new panel of cfRNAs for a pan‐tumour liquid biopsy approach and demonstrated its utility as a prognostic, therapy‐monitoring tool independent of the melanoma mutational genotype. Abstract : Biomarker candidates were identified through unsupervised data mining of melanoma versus benign nevi or healthy skin transcriptomes. Droplet digital PCR (ddPCR) assays were developed for circulating cell‐free RNA (cfRNA) quantification. KPNA2, DTL, BACE2 and DTYMK cfRNA demonstrated high diagnostic accuracy in melanoma. High baseline cfRNA levels were associated with significantly shorter progression‐free survival. cfRNA copies significantly increased during therapy in non‐responders regardless of therapy and mutational subtypes.